Review on Reactive Power Compensation in Short Transmission Line (International Journal of Engineering and Computer Science, 2016)
Flexible AC Transmission Systems (FACTS) devices is the most advanced devices for power flow control in short transmission line, medium transmission line and long transmission line. Awareness of power quality and power flow is big deal in power system because voltage sags, swells, harmonics etc. are the various power quality problem as well as power flow problem. Short transmission line are considered as uncompensated short transmission line and then compensated short transmission line with different FACTs devices are Reviews. Review of reactive power compensation through different research review and author. These papers are focused on problem related to reactive power compensation.